Confronting the Yugoslav controversies : a scholars' initiative - Ingrao, Charles W.; Emmert, Thomas Allan, 1945- (Washington, D.C. : United States Institute of Peace Press ; West Lafayette, Ind. : Purdue University Press, 2013)
It has been two decades since Yugoslavia fell apart. The brutal conflicts that followed its dissolution are over, but the legacy of the tragedy continues to unsettle the region. Reconciliation is a long and difficult process that necessitates a willingness to work together openly and objectively in confronting the past. Over the past ten years the Scholars? Initiative has assembled an international consortium of historians, social scientists, and jurists to examine the salient controversies that still divide the peoples of former Yugoslavia. The findings of its eleven research teams represent a direct assault on the proprietary narratives and interpretations that nationalist politicians and media have impressed on mass culture in each of the successor states. Given gaps in the historical record and the existence of sometimes contradictory evidence, this volume does not pretend to resolve all of the outstanding issues. Nevertheless, this second edition incorporates new evidence and major developments that have taken place in the region since the first edition went to press. At the heart of this project has always been the insistence of the authors that they would continue to reconsider their analyses and conclusions based on credible new evidence. Thus, in this second edition, the work of the Scholars' Initiative continues. The broadly conceived synthesis will assist scholars, public officials, and the people they represent both in acknowledging inconvenient facts and in discrediting widely held myths that inform popular attitudes and the electoral success of nationalist politicians who profit from them. Rather than rely on special pleading and appeals to patriotism that have no place in scholarship, the volume vests its credibility in the scientific credentials of its investigators, the transparent impartiality of its methodology, and an absolute commitment to soliciting and examining evidence presented by all sides.
The dissolution of Yugoslavia / Andrew Wachtel and Christopher Bennett -- Kosovo under autonomy, 1974-1990 / Momcilo Pavlovic -- Independence and the fate of minorities, 1991-1992 / Gale Stokes -- Ethnic cleansing and war crimes, 1991-1995 / Marie-Janine Calic -- The international community and the fry/belligerents, 1989-1997 / Matjaz Klemencic -- Safe areas / Charles Ingrao -- The war in Croatia, 1991-1995 / Mile Bjelajac and Ozren Zunec -- Kosovo under the Milosevic regime / Dusan Janjic, with Anna Lalaj and Besnik Pula -- The war in Kosovo, 1998-1999 / James Gow -- The International Criminal Tribunal for the Former Yugoslavia / John B. Allcock, editor -- Living together or hating each other? / David MacDonald, editor -- Montenegro : a polity in flux, 1989-2000 / Kenneth Morrison.
Includes bibliographical references and index.
Print version record.
eBooks on EBSCOhost
Keywords: Yugoslavia -- History -- 1992-2003.; Former Yugoslav republics -- History; Yugoslavia -- Ethnic relations -- History -- 20th century; Former Yugoslav republics -- Ethnic relations -- History -- 20th century; Ethnic conflict -- Yugoslavia -- History -- 20th century; Ethnic conflict -- Former Yugoslav republics -- History -- 20th century; Yugoslav War, 1991-1995.; Kosovo War, 1998-1999.; Kosovo (Republic) -- History -- 1980-2008.; Yougoslavie -- Histoire -- 1992-2003.; Yougoslavie -- Relations interethniques -- Histoire -- 20e siècle.; Conflits ethniques -- Yougoslavie -- Histoire -- 20e siècle.; Conflits ethniques -- Ex-Yougoslavie -- Histoire -- 20e siècle.; Guerre dans l'ex-Yougoslavie, 1991-1995.; Kosovo -- Histoire -- 1980-2008.; Ex-Yougoslavie -- Histoire; Ex-Yougoslavie -- Relations interethniques -- Histoire -- 20e siècle.; Guerre du Kosovo, 1998-1999.; HISTORY -- Europe -- General; HISTORY -- Europe -- Former Soviet Republics; POLITICAL SCIENCE -- Political Ideologies -- Nationalism & Patriotism; Ethnic conflict; Ethnic relations; Kosovo (Republic); Serbia; Yugoslavia; 1900-2008; Electronic books; History